Consumer Satisfaction and Loyalty Towards Chatime Beverage Products: Evidence from Pekanbaru, Indonesia - Noviasari, Henni; Junaidi, Andi; Wildah, Sri Wahyuni; Azmi, Fauzan; Ishadi, Ishadi; Siregar, Prima Andreas (West Science Business and Management, 2024)
This study examines the influence of taste, price, and service quality on consumer satisfaction and loyalty towards Chatime beverage products in Pekanbaru, Indonesia. Understanding consumer behavior is crucial for sustaining business growth in the rapidly growing food and beverage industry. By leveraging theories of consumer satisfaction and loyalty, this study adopts a quantitative approach through multiple regression analysis of data collected from 108 respondents. The findings revealed that taste, price, and service quality significantly affect consumer satisfaction and loyalty. Interestingly, while satisfaction significantly fosters loyalty, it does not mediate the relationship between price and loyalty, suggesting price sensitivity among students’ demographics. Despite perceiving Chatime's products as relatively expensive, their willingness to recommend the brand indicates recognition of quality. This study contributes to a nuanced understanding of the factors driving consumer loyalty in the competitive beverage industry, emphasizing the need for strategic pricing and quality enhancement to foster consumer satisfaction and loyalty.